EXPANDING LANGUAGE LEARNING OPPORTUNITIES THROUGH COMICS - Rajeswari, Dr. S. (International Journal of Psychosocial Rehabilitation, 2020)
Various methods help language learners develop critical thinking, independence and problem-solving abilities. The present study examines how Comic strips provide a unique and exciting way to engage language learners in the world of English. The findings are significant that unplanned interactions create gap between theory and practice. Using comics in English classroom is about harnessing students’ natural interests. Comic strips can be used from beginner level to advanced level for a variety of language activities and discussion activities as an expanding language learning opportunity. In the development of innovation comics enhance competency in expanding language learning by reducing the gap between theory and practice. Comics can be displayed digitally like animation. They can also be delivered in the form of overhead projector or in print form. This allows comics to be functional even in an English classroom that is not set up for the use of modern technology. The results suggest that Comics’ content is easier to manage. They assist in decision-making and allow students to represent a professional situation based on theoretical precepts. Comics demand understanding the nature of the student- teacher relationship and the relationships among the students.